The Concept of Ma in Western Art Music: From Religious Architecture to the Interpretation of Time - Marty, Luca (Schweizer Jahrbuch für Musikwissenschaft, 2026)
Ma is clearly rooted in religious and spiritual practice, foremost in the Shinto tradition. It is an important concept in Japanese culture, influencing all art forms. Ma relates to the Japanese unification of the concepts known in the West as space and time. Therefore, it is applicable to both the performing and visual arts, in other words, to arts in time and arts in space.Beyond its metaphysical dimension, Ma also has a technical meaning in the arts, which affects the performance practice of Japanese music. I am particularly interested in this technical aspect, especially in terms of how it influences the interpretation of Western art music by Japanese composers. As it suggests a degree of rhythmic freedom granted to the performer, it contrasts with the prevailing paradigm of rhythmic rigor in Western art music. An issue that will be explored in my thesis.As a theoretical foundation, I focus on approaches from ethnomusicology and interpretation research, connecting theories of the Kyoto School with Foucault’s concept of technologies of the self. I aim to develop my own theoretical framework based on grounded theory.The final outcome of this research will be the development of guidelines to assist performers in interpreting contemporary Japanese music.